Optimization of vitexin and isovitexin compounds extracted from dried Mas Cotek leaves using one-factor-at-a-time (OFAT) approach in aqueous extraction - Nasma, A.; Aisyah, Naila; Azilah, Ajit; Ahmad Ziad, Sulaiman (Penerbit Universiti Putra Malaysia, 2018)
Mas Cotek or Ficus deltoidea is regarded as one of the most precious herbal plants in Malaysia due to its content of beneficial active compounds and appreciation as a traditional remedy. This research investigated performance of aqueous or water extraction of dried Mas Cotek leaves for vitexin and isovitexin compounds using three regiments of temperatures (50, 70 and 100°C) in sample-to-water ratios of 1:10, 1:20 and 1:30g/mL during 8 hours of extraction. The optimum yield recorded for vitexin compound was 0.463 ± 0.045 (%w/w) from; 1:30 g/mL sampleto-water ratio, 50°C temperature at 4th hour of extraction. While for isovitexin compound, the optimum value recorded was 0.136 ± 0.015 (%w/w) from; 1:20 (g/mL) sample-to-water ratio, 50°C temperature at 5th hour of extraction. The morphological characterization of the extracted dried leaves particles performed using FE-SEM showed an intact and less damaged surface of extracted sample after 8 hours of extraction. The experimental values under best conditions were consistent with the predicted values, which suggested that aqueous extraction of Mas Cotek leaves is a good platform to serve as baseline study for more advanced extraction techniques.